Molecular Dynamics Simulation of Ibuprofen Crystal Polymorph - Mohammad Safuan, Mat Noor (2012)
Ibuprofen (iso-butyl-propanolic acid) is one of the Active Pharmaceutical Ingredients (API) that uses to treat a symptom of rheumatism, arthritis, fever, as an analgesic (pain reliever). This study aims to identify which solvents should affect the polymorph of ibuprofen begins from the crystallization solution. The Molecular Dynamics Simulation and Fourier transform infrared (FTIR) is used to recognize which molecules that form hydrogen bond in the ibuprofen crystal polymorph. The study analysis has shown that the higher hydrogen bond between the atoms will contribute to the ibuprofen crystal polymorph. As the conclusion, only the selected atoms will contribute in the formation of desired crystal polymorph of ibuprofen.